The Effect of Combined SEFT and SPEOS Therapy on Anxiety and Breast Milk Production in Postpartum Women: A Quasi-Experimental Study - Mona, Silvia; Dasaryandi, Kiki Rizki; Susanti, Susanti (Majalah Kesehatan Indonesia, 2025)
Postpartum anxiety affects approximately 30–40% of mothers and can reduce breast milk production by inhibiting the let-down reflex. Effective and holistic non-pharmacological interventions are still limited. This study aimed to test the effectiveness of the combination of SEFT and SPEOS therapy in addressing anxiety and increasing breast milk production in the postpartum period. This study used a quasi-experimental pretest–posttest design with a control group. A total of 48 postpartum mothers who met the inclusion criteria were divided into intervention and control groups using a purposive sampling technique. The intervention group received a combination of Spiritual Emotional Freedom Technique therapy and Endorphin, Oxytocin, and Suggestive Massage Stimulation for eight sessions (4 weeks) lasting 30–45 minutes. Anxiety levels were measured using the Postpartum Specific Anxiety Scale (PSAS), while breast milk production was recorded based on volume. Data were analyzed using a paired t-test. The results of this study indicate that the combination of SEFT and SPEOS therapy effectively reduces anxiety and significantly increases breast milk production (p < 0.05). The combination of SEFT and SPEOS is a non-pharmacological intervention that contributes practically to midwifery services to support successful exclusive breastfeeding and theoretically expands understanding of the interaction of psychological and neurohormonal factors in lactation.